İdari işlemin konu unsuru - Göçgün, Muhammed (My University, 2016)
2577 sayılı İdari Yargılama Usulü Kanunu'nun 2. maddesindeki düzenleme doğrultusunda idari işlemin unsurlarının yetki, şekil, sebep, konu ve maksat olduğu kabul edilmiştir. Bu unsurlar arasında yer alan ve idari işlemin doğurduğu hukuki sonucu ifade eden konu unsuru, idari işlemin en önemli ve geniş kapsamlı unsurudur. Bu kanaat; özellikle, konu unsurunun idari işlemin özellikleriyle olan irtibatı ve işlemin bizzat içeriğine ilişkin bir unsur olması neticesinde hasıl olmuştur. Zira idari işlemin; icrailik, idari işleve ilişkin olma, hukuka uygunluk karinesinden yararlanma ve tek yanlılık özellikleri de esasında işlemin hukuk aleminde meydana getireceği değişiklikle alakalıdır. İdari işlemin konu unsuru bakımından üzerinde durulması gereken diğer bir husus ise konu unsurunun belirlenmesidir. Kural olarak idari işlemin ortaya çıkaracağı sonuç mevzuatta gösterilir. Bununla birlikte yasama organı ve idare, idari işlemin konu unsurunun belirlenmesi aşamasında kanunilik ve normlar hiyerarşisi ilkeleri çerçevesinde hareket etmelidir. Bu aşamada kanun koyucu, idareyi bağlı yetki içine sokabileceği gibi, idareye işlemin konu unsuruna yönelik takdir yetkisi de tanıyabilir. Önemli olan asli nitelikteki yasama yetkisinin idareye bırakılmamasıdır. Bunun için Anayasa'da kanunla düzenlenmesi öngörülen konularda temel ilkelerin mutlaka kanunda yer alması ve idarenin kullanacağı yetkinin kanun koyucu tarafından sınırlandırılmış olması gerekir. İdari işlemin konu unsuru yönünden hukuka uygunluğunu sağlayan temel ilkeler ise eşitlik, hukuki güvenlik ve ölçülülüktür. Bu üç ilke de idari işlemin ortaya çıkaracağı hukuki sonuca ilişkin olup bu ilkelerin ihlali durumunda, idari işlemin konu unsuruna tekabül eden hukuka aykırılıklar ortaya çıkar. Ne var ki; idari işlemin yargısal denetimi aşamasında idari yargıç, sözü edilen ilkeler kapsamında ortaya çıkan hukuka aykırılıkları gerekçelendirirken bu ilkelerin işlemin konu unsurunu ilgilendirdiğine değinmemektedir. Bu durum, konu unsurunun idari işlemin en zor tespit edilen ve en geniş kapsamlı unsuru olarak kabul edilmesindeki en temel etkenlerdendir.

It is accepted that the elements of administrative act in terms of the regulation in Article 2 of Administrative Procedure Law No. 2577 are power, form, reason, subject and purpose. Among these elements, the subject element, which expresses the legal result of the administrative act is the most important and comprehensive element. This opinion is based on the connection between the subject element and the features of the administrative act and the fact that the subject element is is concerned with the content of the administrative act itself. Because, the features of administrative act that are unilateralism, executability, being in relation to the administrative function and to benefit from the legality presumption are related to the change that the administrative act will bring about in the world of law. Another issue that needs to be considered in terms of the subject element of the administrative act is the determination of the subject element. As a rule, the result of the administrative act is stated in the legislation. However the administration and the legislative body must act in accordance with legality and the hierarchy of norms while determining the subject element of the administrative act. The legislative authority may insert administration into the dependent power or may also allow discretionary power to determine the subject element of the administrative act. It is important that the primary legislative power is not allowed to the administration. To provide this, the basic principles must be included in the act, in matters that should be regulated by act in accordance with the constitution and it must be limited to the power which the administration will use by the legislator. It is worth considering that the criteria established by the Constitutional Court through its decisions on this issue regarding the lawfulness of the laws and administrative acts in terms of the subject element. The basic principles that ensure compliance with the law in terms of the subject element of administrative act are equality, legal security and moderation. These three principles relate to the legal consequences of the administrative act, and in the event of violation of these principles, there arises a breach of law corresponding to the subject element of the administrative act. However, the administrative judge in the course of judicial review of administrative act does not refer to the fact that these principles are concerned with the subject element of the administrative act, while justifying the contradictions that arise under the mentioned principles. This is one of the most important factors why the subject matter is considered to be the most difficult and most comprehensive element of the administrative act.
Keywords: İdari işlemler; Kamu hukuku; Türkiye